COMPLEX EVALUATION OF WORKING CONDITIONS IN GALVANIC WORKSHOPS - A. M. Lazarenkov; S. A. Khoreva; V. V. Melnichenko (Литьë и металлургия, 2013)
The results of complex evaluation of working conditions in galvanic workshops, and based on research of industrial environmental factors jobs are given. The hygienic overview of working conditions classification in working stations of galvanic workshops is given.